KINETIKA MIKRO DEKOMPOSISI METANA MENJADI KARBON NANOTUBE PADA PERMUKAAN KATALIS Ni-Cu-Al - Praswasti Pembangun Dyah Kencana Wulan; Widodo Wahyu Purwanto; Yuswan Muharam (Reaktor, 2011)
MICRO KINETICS OF DECOMPOSITION OF METHANE TO CARBON NANOTUBES OVER NI-CU-AL CATALYST. The main focus of this research was to obtain micro kinetics decomposition of methane producing carbon nanotube on the surface of the Ni-Cu-Al catalyst. Experimental kinetics data collected at a temperature range of 650-750oC and pressure of one atmosphere. The preliminary test was conducted to obtain the kinetics are not influenced by external and internal diffusion limitations as well as inter-phase transfer. Kinetics data were tested by micro kinetic model derived from the catalyst surface reaction mechanism. The most appropriate kinetic model becomes the rate-limiting step of methane decomposition reaction. Results of preliminary experiment showed that the kinetics of the external diffusion effect is negligible at flow rates above 150 mL/min. Internal diffusion can be ignored with a catalyst under 0.25 mm in diameter with a weight of 0.04 grams of catalyst and contact time 2.5x10-4. Rate equation analysis shows that the rate-limiting step is the adsorption which indicates that intermediate consumption (CH4I + I Û CH3I + HI) is faster than the formation of intermediate (adsorption of methane, CH4 + I Û CH4I). The activation energy obtained for 34.628 kJ/mol and pre-exponential factor of 6.583x106.  Fokus utama penelitian ini adalah memperoleh kinetika mikro dekomposisi metana yang menghasilkan Carbon Nanotube pada permukaan  katalis Ni-Cu-Al. Data kinetika eksperimen diambil pada rentang temperatur 650-750oC dan tekanan 1 atmosfer. Percobaan pendahuluan dilakukan untuk memperoleh daerah kinetika yang tidak dipengaruhi oleh limitasi difusi eksternal dan internal serta perpindahan antar fasa.  Data kinetika  diuji dengan model kinetika mikro yang diturunkan dari mekanisme reaksi permukaan katalis. Model kinetika yang paling sesuai menjadi tahap pembatas laju reaksi dekomposisi metana. Hasil percobaan pendahuluan kinetika menunjukkan bahwa pengaruh difusi eksternal dapat diabaikan pada laju alir di atas 150 mL/menit. Difusi internal dapat diabaikan dengan menggunakan katalis berdiameter di bawah 0,25 mm dengan berat katalis 0,04 gram pada waktu kontak 2,5x10-4. Analisis persamaan laju menunjukkan bahwa tahap pembatas laju adalah tahap adsorpsi yang menunjukkan bahwa konsumsi intermediate (CH4I + I Û CH3I + HI) lebih cepat dari pembentukan intermediate (adsorpsi metana,CH4 + I Û CH4I). Energi aktivasi yang diperoleh sebesar 34,628 kJ/mol dan faktor pre-eksponensial 6,583x106.